2004
DOI: 10.1007/s10340-004-0062-5
|View full text |Cite
|
Sign up to set email alerts
|

Introducing GIS-modelling into the management of a brown rat (Rattus norvegicus Berk.) (Mamm. Rodentia Muridae) population in an urban habitat

Abstract: The landscape of three test areas of an urban environment was efficiently assessed for its ability to support brown rats (Rattus norvegicus Berk.) by successfully integrating habitat suitability modelling using GIS (Geographical Information System). The GIS model, validated using an independent set of rat observations, and a model analysis showed the potential of different habitats for rat occurrence. Because of its use of general land-cover types, the model could be applied to other cities. This model system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 11 publications
4
25
1
Order By: Relevance
“…In the present study the location of the households on an earthen slope was identified as an independent risk factor for infestation. Similar results were found in previous studies 24,29,31 . Households built on an incline provide suitable space for rodent harborage, and the preference of R. norvegicus to select slopes to build burrows was registered in a previous study 32 .…”
Section: Variablessupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study the location of the households on an earthen slope was identified as an independent risk factor for infestation. Similar results were found in previous studies 24,29,31 . Households built on an incline provide suitable space for rodent harborage, and the preference of R. norvegicus to select slopes to build burrows was registered in a previous study 32 .…”
Section: Variablessupporting
confidence: 93%
“…identified R. norvegicus as the dominant species in the urban ecosystem of Salvador 4 , brown rat feces represented 80% of the rodent feces in our study. This pattern is also observed in other urban areas around the world 22,24,25,26,27,28,29,30 .…”
Section: Discussionsupporting
confidence: 64%
“…All these successful hair traps had been placed in a city area called ''Lehen'', an apartment house settlement with a high density of inhabitants and poor hygienic situation. In accordance, the presence of a possible rat population in this area was also predicted by the results of a GIS model which we conducted for the city of Salzburg (Traweger and Slotta-Bachmayr 2005). …”
Section: Resultsmentioning
confidence: 94%
“…Nevertheless, the Norway rat was the predominant species in Europe (Austria, Denmark and United Kingdom) and in USA (Leirs et al 2004;Traweger et al 2006;DEFRA 2005;Easterbrook et al 2007). This difference may be due to several factors: roof rat seems to be the predominant species in developing countries, maybe due to precariousness of habitations and environmental sanitation, and the Norway rat in developed countries, where it lives mainly in natural places, such as stream banks, sewer system, vacant lots, parks, gardens, and farms (DEFRA 2005;Traweger and Slotta-Bachmayr 2005;Channon et al 2006;Traweger et al 2006); on the other hand, roof rat seems to be related to warm climates, while Norway rat may dominate in cities with cold climates, as pointed out by Cavia et al (2009). Although these are attractive hypotheses, they still need supporting evidence studies, since there are some conflicting results: in Durban (South Africa), the main species is the Norway rat (Taylor et al 2008) and, even in Sao Paulo city, different boroughs present different infestation patterns by species.…”
Section: Discussionmentioning
confidence: 99%